2023
DOI: 10.1371/journal.pgph.0001179
|View full text |Cite
|
Sign up to set email alerts
|

The integration of tuberculosis and HIV testing on GeneXpert can substantially improve access and same-day diagnosis and benefit tuberculosis programmes: A diagnostic network optimization analysis in Zambia

Abstract: Diagnostic network optimization (DNO), a geospatial optimization technique, can improve access to diagnostics and reduce costs through informing policy-makers’ decisions on diagnostic network changes. In Zambia, viral load (VL) testing and early infant diagnosis (EID) for HIV has been performed at centralized laboratories, whilst the TB-programme utilizes a decentralized network of GeneXpert platforms. Recently, the World Health Organization (WHO) has recommended point-of-care (POC) EID/VL to increase timely d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Before the introduction of the referral system, the results showed that both tests (VL and EID) were equally prioritized in terms of reducing the overall TAT, and this also correlated with the DBS sample used for EID and the plasma sample for VL testing. In 2017, the Ministry of Health supported the deployment of point-of-care (POC) EID/VL and the use of diagnostic network optimization (DNO) to improve facility testing and demand creation [ 24 ]. This assisted in reducing the demand for sample couriers in centralized testing.…”
Section: Discussionmentioning
confidence: 99%
“…Before the introduction of the referral system, the results showed that both tests (VL and EID) were equally prioritized in terms of reducing the overall TAT, and this also correlated with the DBS sample used for EID and the plasma sample for VL testing. In 2017, the Ministry of Health supported the deployment of point-of-care (POC) EID/VL and the use of diagnostic network optimization (DNO) to improve facility testing and demand creation [ 24 ]. This assisted in reducing the demand for sample couriers in centralized testing.…”
Section: Discussionmentioning
confidence: 99%
“…As molecular testing can detect multiple infectious diseases, implementation of molecular testing could enable a diverse range of tests to be carried out in tandem, for example, TB, HIV viral load, SARS-CoV-2, sexually transmitted infections, respiratory syncytial virus, influenza and human papilloma virus, to name a few. Indeed, reports have highlighted the value of integrating TB and HIV testing 10 , and TB and SARS-CoV-2 testing 11 . Comment difficult in young children and people living with HIV.…”
Section: Multi-disease Testing Must Replace Single-disease Testingmentioning
confidence: 99%
“…Second, India has already purchased nearly 5000 CB-NAAT systems (Xpert MTB/RIF as well as TrueNAT), and thus has a good network available to build on and optimize via Diagnostic Network Optimization (DNO). DNO, a geospatial analytics approach that uses optimization techniques to model a diagnostic network and ensure greatest access to services, while maximizing the overall efficiency of the system, has been successfully used in countries such as Zambia and Lesotho 15 , 16 . However, machines without cartridges are a dead investment.…”
Section: The Case For India To Transition To Large-scale Molecular Te...mentioning
confidence: 99%